Tumor necrosis factor α and RANKL blockade cannot halt bony spur formation in experimental inflammatory arthritis - Schett, Georg; Stolina, Marina; Dwyer, Denise; Zack, Debra; Uderhardt, Stefan; Krönke, Gerhard; Kostenuik, Paul; Feige, Ulrich (Arthritis and Rheumatism, 2009)
Objective. To investigate the kinetics of bony spur formation and the relationship of bony spur formation to synovial inflammation and bone erosion in 2 rat arthritis models, and to address whether bony spur formation depends on the expression of tumor necrosis factor α (TNFα) or RANKL. Methods. Analysis of the kinetics of synovial inflammation, bone erosion, osteoclast formation, and growth of bony spurs was performed in rat collagen-induced arthritis (CIA) and adjuvant-induced arthritis (AIA). In addition, inhibition experiments were performed to assess whether inhibition of TNFα and RANKL by pegylated soluble TNF receptor type I (pegTNFRI) and osteoprotegerin (OPG), respectively, affected bony spur formation. Results. Bony spurs emerged from the periosteal surface close to joints, and initial proliferation of mesenchymal cells was noted as early as 3 days and 5 days after onset of CIA and AIA, respectively. Initiation of bony spur formation occurred shortly after the onset of inflammation and bone erosion. Neither pegTNFRI nor OPG could significantly halt the osteophytic responses in CIA and AIA. Conclusion. These results suggest that bony spur formation is triggered by inflammation and initial structural damage in these rat models of inflammatory arthritis. Moreover, emergence of bony spurs depends on periosteal proliferation and is not affected by inhibition of either TNFα or RANKL. Bony spur formation can thus be considered a process that occurs independent of TNFα and RANKL and is triggered by destructive arthritis. © 2009, American College of Rheumatology.
CRIS-Team Scopus Importer:2020-11-20